«¿Quién limpia los pájaros después?». La obra del fotógrafo brasileño Tony Genérico entre el arte y la ciencia - Mtr. Elisa TAVARES DUARTE (Fonseca, Journal of Communication, 2023)
The present work aims to analyze photography as an edge between art and science, centered on the Threatened Beauty project, developed since 2004 by the Brazilian photographer Tony Genérico. This project consists of a set of photographs of birds at risk of extinction, produced from the combination of high-speed and splash techniques. For this, the main source of the study is an interview carried out by the author to the photographer,which shows his biographical and professional trajectory.